2016
DOI: 10.1139/apnm-2015-0543
|View full text |Cite
|
Sign up to set email alerts
|

Acute cocoa flavanol supplementation improves muscle macro- and microvascular but not anabolic responses to amino acids in older men

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 85 publications
(86 reference statements)
4
21
0
Order By: Relevance
“…Capillary density and endothelial function are also good indicators of microvascular function-both have been shown to decline with age and improve in response to exercise training [26,27]. It has been suggested that reduced microvascular blood flow may contribute to the anabolic resistance of muscle [28] which is observed with advancing age [20,29,30], however, data on this is not yet conclusive [31].…”
Section: Introductionmentioning
confidence: 99%
“…Capillary density and endothelial function are also good indicators of microvascular function-both have been shown to decline with age and improve in response to exercise training [26,27]. It has been suggested that reduced microvascular blood flow may contribute to the anabolic resistance of muscle [28] which is observed with advancing age [20,29,30], however, data on this is not yet conclusive [31].…”
Section: Introductionmentioning
confidence: 99%
“…These data are the first to demonstrate that acute NO 3 Ϫ supplementation does not represent an effective nutritional strategy to enhance postprandial protein handling in vivo in humans. As acute dietary interventions to restore vascular function do not appear to increase postprandial muscle protein synthesis rates (13,37,41), longer-term intervention studies involving chronic supplementation of NO substrates may be necessary to enhance vascular function and augment the anabolic response to protein ingestion (30,48,59 …”
Section: E331 Dietary Nitrate Co-ingestion and Muscle Protein Synthesismentioning
confidence: 99%
“…Micro‐needle biopsies are a less traumatic alternative to the Bergström needle, with a yield of about 20 mg or less. The conchotome procedure provides tissue yields comparable to the Bergström needle . Open biopsies—which are preferred in the diagnosis of some forms of myositis—can provide greater than 1000 mg of muscle tissue but can be more traumatic.…”
Section: Introductionmentioning
confidence: 99%
“…The conchotome procedure provides tissue yields comparable to the Bergström needle. 6 Open biopsies-which are preferred in the diagnosis of some forms of myositis-can provide greater than 1000 mg of muscle tissue 1 but can be more traumatic. Dorph et al 7 however reported comparable myositis detection rates when comparing open biopsies with repeated conchotome biopsies.…”
mentioning
confidence: 99%
See 1 more Smart Citation